Effects of Wage and Price controls in Canada: 1975-1978 - Staudohar, Paul (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1979)
The author examines the recent Canadian experience in wage and price controls» including an analysis of these controls, the problems confronting their implementation, and certain of their results.